Model Pengembangan Daya Saing UMKM pada Era Pandemi di Kota Jambi - Ahmad Soleh; Esti Susilawati; Siswoyo Siswoyo (Universitas Batanghari, 2022)
This research aims to analyze: (1) Jambi MSMEs profile both from the internal and external side used qualitative descriptive analysis with statistical approaches, ratio models, growth; (2) What factors determine the competitiveness of MSMEs in Jambi City then used sem model and; (3) How the best strategy in improving MSME Competitiveness is used SWOT and FGD Analysis Models. The study used secondary data and primary data. Secondary data is obtained from literature and related agencies. While the primary data is obtained through interviews, surveys and questionnaires with random sampling methods with a non probability sampling approach (Slovin). This research is Exploratory using quantitative and qualitative descriptive methods with a Sequential Exploratory Design approach. The research site was conducted in Jambi City with a sample of 389 respondents. The results showed that the condition of MSMEs in Jambi City showed significant and equitable development and had good potential for the development of MSMEs in the future and had a low level of education, immigrants from outside, their own, MSMEs are still dominated by culinary businesses, the average range of actors has been running a business for 5 years, traditional pasih marketing system and local area marketing area. While the policy strategy that can be done to increase MSMEs in Jambi City is carried out by referring to SWOT analysis by considering from the aspects of marketing, labor, production and marketing and then continued with support for innovation development.